2016
DOI: 10.1117/1.oe.55.6.066112
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-coated fiber Bragg grating sensor for pH monitoring

Abstract: We present a fiber-optic wavelength-modulated sensor for pH applications. Fiber Bragg grating (FBG) is functionalized with a stimulus-responsive hydrogel that induces a strain on FBG due to mechanical expansion of the gel in response to ambient pH changes. The gel is synthesized from the blends of poly (vinyl alcohol)/poly (acrylic acid). The induced strain results in a shift of FBG reflected peak that is monitored by an interrogator. The sensor system shows good linearity in the acidic pH range of 3 to 7 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…decrease the amount of axial force needed to produce a certain value of strain. For instance, this is highly useful when using the FBG in combination with a transducer for chemical sensing and biosensing applications [5]- [8]. This can be achieved by reducing A in eq.…”
Section: Introductionmentioning
confidence: 99%
“…decrease the amount of axial force needed to produce a certain value of strain. For instance, this is highly useful when using the FBG in combination with a transducer for chemical sensing and biosensing applications [5]- [8]. This can be achieved by reducing A in eq.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber Bragg grating (FBG) sensors coated with pH-sensitive hydrogel have been studied through a simulation, which showed that they can provide a linear response in the pH range of 5 to 7 with a sensitivity of 0.164 nm/pH unit [9], [10]. Optical pH sensors have advantages compared to the conventional ones, being free from electromagnetic interference, having wide bandwidth, being open to miniaturization, real-time measurement and remote sensing [11]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…Multilayers of PVA/PAA were deposited on FBGs by the dip‐coating method for developing a pH sensor. [ 19 ] The hydroxyl groups of PVA and the carboxyl groups of PAA were cross‐linked by heating up the multilayers. The fiber sensor showed a linear response to pH in the range of 3–7, presenting a sensitivity of 0.0122 nm pH −1 resulting from the change of the swelling degree of the hydrogel in different pH conditions.…”
Section: Fiber Bragg Gratings (Fbgs)mentioning
confidence: 99%